Redes de Sensores Sem Fio (RSSF) para monitoramento por geolocalização para pecuária: estudo de caso empregando o simulador NS-2 - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This work presents a study on wireless sensor networks (WSNs) for geolocation monitoring for livestock using the Network Simulator 2 (NS-2) simulation software. In order to verify the duration of the WSN, it is analyzed the impact of the routing protocol employed in the network and the number of nodes of the WSN network, in addition to the packet transmission interval. As case studies, wireless sensor networks composed of one concentrator and fifteen, thirty, and forty-five sensor nodes were used, in addition to five minutes and ten minutes transmission intervals. Three unicast routing protocols were analyzed: Ad Hoc On-Demand Distance Vector Routing (AODV), Dynamic Source Routing (DSR) and Destination Sequenced Distance Vector (DSDV). Performance metrics such as overhead, throughput, packet delivery ratio (PDR), average network delay and average power consumption were compared to evaluate the impact of using different protocols. Each simulated node consists of an Arduino Uno, a nRF905 transceiver, and one GPS module. The obtained results indicate that the DSR protocol provides a longer RSSF lifetime in the scenario with transmission interval of five minutes, and the AODV protocol presented a better performance for transmission interval of ten minutes, and in none of the scenarios, the DSDV protocol presented better performance than the other protocols.
Keywords: Engenharia de telecomunicação; Redes sensores sem fio; Network simulator; Telecommunication engineering; Wireless sensor network; CNPQ::ENGENHARIAS